2003
DOI: 10.1097/01.rhu.0000062514.54375.bd
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Risk of Continuous Leflunomide Treatment on the Incidence of Infectious Complications After Joint Arthroplasty in Patients With Rheumatoid Arthritis

Abstract: To determine whether the risk of infectious complications after total joint arthroplasty is increased in rheumatoid arthritis patients who are treated continuously with leflunomide, the incidences of infectious complications in 41 rheumatoid arthritis patients who received continuous leflunomide treatment (leflunomide group) and in 41 patients who did not receive leflunomide within 4 weeks of surgery (nonleflunomide group) were compared. The incidence (6.1%) of local infection after surgery in the leflunomide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 6 publications
0
28
0
8
Order By: Relevance
“…Другие ре-зультаты получили N. Tanaka и соавт. [50], которые в боль-шом проспективном исследовании разделили 161 пациен-та с РА, перенесших эндопротезирование, на две группы. В одной из них больные продолжали непрерывный прием ЛЕФ, в другой ЛЕФ отменяли за 2 нед до и возобновляли его прием через 2 нед после операции.…”
Section: таблицаunclassified
“…Другие ре-зультаты получили N. Tanaka и соавт. [50], которые в боль-шом проспективном исследовании разделили 161 пациен-та с РА, перенесших эндопротезирование, на две группы. В одной из них больные продолжали непрерывный прием ЛЕФ, в другой ЛЕФ отменяли за 2 нед до и возобновляли его прием через 2 нед после операции.…”
Section: таблицаunclassified
“…A significant increase in wound healing complications has been reported in leflunamide-treated patients (40%) compared with MTXtreated patients (13.6%) [28]. However, a contrasting study found no difference comparing 41 patients given continuous leflunamide when compared with 41 patients in whom the leflunamide was stopped 1 month prior to surgery [29]. Pending definitive studies, we recommend holding leflunamide and sulfasalazine until normal postoperative bowel and renal function has been demonstrated.…”
Section: Medicationsmentioning
confidence: 94%
“…All patients who developed infection were also taking prednisone in addition to their leflunomide. However, corticosteroids were also not found to be associated with higher risk of infection [35] . In contrast, in another prospective study, patients with predominantly RA were prospectively followed as they continued leflunomide therapy during the perioperative time period.…”
Section: Biologicsmentioning
confidence: 98%